No health without access: using a retrospective cohort to model a care continuum for people released from prison at an urban, safety net health system - Michael Frank; Ryan Loh; Rachel Everhart; Hermione Hurley; Rebecca Hanratty (BMC, 2023)
Abstract Background Release from prison is characterized by discontinuity of healthcare services and results in poor health outcomes, including an increase in mortality. Institutions capable of addressing this gap in care seldom collaborate in comprehensive, data-driven transition of care planning. This study harnesses information from a data exchange between correctional facilities and community-based healthcare agencies in Colorado to model a care continuum after release from prison. Methods We merged records from Denver Health (DH), an urban safety-net healthcare system, and the Colorado Department of Corrections (CDOC), for people released from January 1 to June 30, 2021. The study population was either (a) released to the Denver metro area (Denver and its five neighboring counties), or (b) assigned to the DH Regional Accountable Entity, or (c) assigned to the DH medical home based on Colorado Department of Healthcare Policy and Financing attribution methods. Outcomes explored were outpatient, acute care, and inpatient utilization in the first 180 days after release. We used Pearson's chi-squared tests or Fisher exact for univariate comparisons and logistic regression for multivariable analysis. Results The care continuum describes the healthcare utilization at DH by people released from CDOC. From January 1, 2021, to June 30, 2021, 3242 people were released from CDOC and 2848 were included in the data exchange. 905 individuals of the 2848 were released to the Denver metro area or attributed to DH. In the study population of 905, 78.1% had a chronic medical or psychological condition. Within 180 days of release, 31.1% utilized any health service, 24.5% utilized at least one outpatient service, and 17.1% utilized outpatient services two or more times. 10.1% utilized outpatient services within the first 30 days of release. Conclusions This care continuum highlights drop offs in accessing healthcare. It can be used by governmental, correctional, community-based, and healthcare agencies to design and evaluate interventions aimed at improving the health of a population at considerable risk for poor health outcomes and death.